To study on the level of satisfaction of comfort level which influenced the space management in shopping malls in Shah Alam / Eveana Crystle Peng Guan - Eveana Crystle Peng Guan (Faculty of Art and Design, 2013)
As we all know in today’s era, the construction of the shopping mall has rapidly increasing as the shopping mall is one of the factorsthat could boost the economic growth in the country. This rapid growth is because of the intention in providing the needs and demand from the people surrounds. Therefore, a good shopping mall could attract publics to enter the building and with this, the management needs to be particular on the comfort level of the people and its employee. Each individual will varies in having the level of comfortness and also this is influenced by the space provided. A good space management needs to be balance with a proper comfort level maintenance as this will gives a satisfactory feeling towards the people.